1990
DOI: 10.1073/pnas.87.11.4304
|View full text |Cite
|
Sign up to set email alerts
|

The ability of Salmonella to enter mammalian cells is affected by bacterial growth state.

Abstract: We have examined the effect of different growth conditions on the ability of Salmonella to interact with Madin-Darby canine kidney cells. Two growth conditions that affect the expression of Salmonella adherence and invasiveness have been identified. First, bacteria lose their invasiveness in the stationary phase of growth. Second, bacteria growing in oxygen-limited growth conditions are induced for adherence and invasiveness, whereas those growing aerobically are relatively nonadherent and noninvasive. Salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
374
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(390 citation statements)
references
References 37 publications
14
374
2
Order By: Relevance
“…The S. typhimurium peptidoglycan structure was shown consistently to be similar to that described for Escherichia coli (Pisabarro et al, 1985;Glauner et al, 1988;Gally and Cooper, 1993). However, in our study we used the highly virulent strain S. typhimurium SL1344, and specific growth conditions, such as non-shaking static growth, to render bacteria competent to infect cultured mammalian cells (Lee and Falkow, 1990). Therefore, an initial study was performed to analyse by HPLC the muropeptide composition of SL1344 grown overnight in LB medium (Lennox, 1995) under nonshaking conditions.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The S. typhimurium peptidoglycan structure was shown consistently to be similar to that described for Escherichia coli (Pisabarro et al, 1985;Glauner et al, 1988;Gally and Cooper, 1993). However, in our study we used the highly virulent strain S. typhimurium SL1344, and specific growth conditions, such as non-shaking static growth, to render bacteria competent to infect cultured mammalian cells (Lee and Falkow, 1990). Therefore, an initial study was performed to analyse by HPLC the muropeptide composition of SL1344 grown overnight in LB medium (Lennox, 1995) under nonshaking conditions.…”
Section: Resultssupporting
confidence: 53%
“…Bacteria were grown overnight in LB medium (Lennox, 1955), at 37ЊC, in static non-shaking conditions (OD 550 = 1.0) when required to infect cultured epithelial cells (Lee and Falkow, 1990). Bacteria were also grown in LB medium, at 37ЊC under shaking conditions (200 r.p.m.…”
Section: Methodsmentioning
confidence: 99%
“…It is particularly well documented that microtubules, which are essential for transport from early to late endosomes, are disrupted by incubation at low temperatures (Matteoni and Kreis, 1989;Gruenberg et al, 1989;D'Arrigo et al, 1997). As the expression of invasion loci in Salmonella, and consequently the invasion process itself, is known to be affected by physiological conditions (Ernst et al, 1990;Lee and Falkow, 1990;Behlau and Miller, 1993;Kusters et al, 1993;Schiemann, 1995), we examined whether ef®cient invasion could be obtained in 5 min by measuring bacterial invasion at various points on the growth curve. We found that S. typhimurium invasion in HeLa cells was most ef®cient when bacteria were grown to late log phase and that bacteria could invade cells ef®ciently within 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that bacterial invasion is affected by growth phase, although, in most cases, investigators have used S. typhimurium grown to stationary phase and have incubated bacteria with cells for a minimum of 15 min, but usually considerably longer (Lee and Falkow, 1990;Behlau and Miller, 1993;Mills and Finlay, 1994;Garcia-del Portillo and Finlay, 1995;Burns-Keliher et al, 1997;Fu and Galan, 1998). Other investigators have synchronized invasion either by centrifuging Salmonella onto cell monolayers or by combining centrifugation with a 48C incubation step to enhance bacterial adhesion further.…”
Section: Optimization Of Invasion Of Hela Cells By S Typhimuriummentioning
confidence: 99%
“…The highly virulent S. Typhimurium strain SL1344 was grown by previously established methods (6). A single inoculum of bacteria was grown in Lysogeny broth under aerated (shaking) conditions at 37°C for 8 h. Cultures at late log phase (OD600 of 0.45-0.65) were collected, washed, and resuspended in sterile PBS at a concentration of 5 3 10 9 CFUs/ml.…”
Section: Colon and Fecal Water Determinationmentioning
confidence: 99%